Speak You So Gently - Tennant, Kylie, 1912-1988 (London Victor Gollancz, 1960)
Recounts the author's trip with Anglican priest Alfred Flint to Aborigines' co-operatives on the Cape York Peninsula and Torres Strait Islands.
Keywords: Missions